Organisational learning capability in SMEs: An empirical development of innovation in the supply chain - Andrew Thomas; Peter Dorrington; Filipa Costa; Gareth Loudon; Mark Francis; Ron Fisher (Cogent Business & Management, 2017)
Evidence that a company's innovation performance, Knowledge Management capability, and its corporate and operational performance are inextricably linked has been the focus of numerous academic studies over recent years. Whilst a significant body of research exists focusing on learning at company level, little research exists on how supply chains learn and innovate in collaborative working environments. The aim of this paper is to determine the learning and innovation skills that emerged from a collaborative project with new developed supply chain. Its focus is on identifying how each organisation within the supply chain developed its Organisational Learning Capability (OLC) when the companies were tasked to collaborate and develop a new and innovative product. The companies had not previously worked with each other and so the project monitored the level of collaborative activity as well as innovative output from the collaboration. The results suggest that improved organistional learning capabilities led to increased levels of organisational innovation as well as improved supply chain collaboration. The paper concludes with the development of a Supply Chain Organisational Learning and Innovation Framework (SCOLIF) and the identification of a number of cultural dimensions which are considered useful for managers and engineers to consider when implementing innovation projects.
Keywords: 650